Measuring the Master Race Physical Anthropology in Norway 1890-1945 - Røyne Kyllingstad, Jon (Open Book Publishers, 2014)
"The notion of a superior 'Germanic' or 'Nordic' race was a central theme in the ideology of the Nazis. But it was also a commonly accepted idea in the early twentieth century, and an actual scientific concept originating from anthropological research on the physical characteristics of Europeans. The Scandinavian Peninsula was considered to be the historical cradle and the core area of this 'master race'. This book investigates the role played by Scandinavian scholars in inventing this so-called superior race, and discusses how this concept put its stamp on Norwegian physical anthropology, prehistory, national identity, and on the Norwegian eugenics movement. It also explores the decline and scientific disputation of these ideas in the 1930s as they came to be associated with the 'genetic cleansing' of Nazi Germany. This is the first comprehensive study on Norwegian physical anthropology, and its findings shed new light on current political and scientific debates about race across the globe."